A needs analysis for the implementation of a complementary course in mathematics education for teachers of mathematics in Namibia: a case study - Ilukena, Alex Mbonabi (Rhodes University, Faculty of Education, Department of Education, 2009)
After the introduction of the Basic Education Teacher Diploma (BETD) in Namibia, a number of studies were conducted on how teachers, lecturers, stakeholders and the Namibian public perceived the BETD program and its implementation. However, very few studies focussed specifically on mathematics subject content knowledge and pedagogical content knowledge in the BETD. The purpose of this study was to investigate the need for a complementary course in mathematics education to address the lack of mathematical content and pedagogical knowledge in the Namibian BETD. The study involved five mathematics school teachers, two mathematics college lecturers in the Kavango educational region and a professor of mathematics education at the University of Namibia. These participants were purposefully selected because of their knowledge and experiences with various aspects of the BETD program. The motivation for conducting this study was to gain a better understanding of some of the issues that have been raised about the BETD program, particularly the perceived inadequacy of mathematical subject content and methodology since the inception of the program. The study adopts a qualitative approach in reporting participants' reflections. The views of the focal educators and documents such as syllabi and course outlines were the main source of data. The findings indicate that despite the training that the three BETD mathematics graduates in this study received, the level of mathematics taught in a complementary course, such as an ACE, would clearly better equip mathematics teachers to teach proficiently and facilitate access to institutions of higher learning such as universities. The results of the study revealed that there was a need for the implementation of a complementary course to the BETD in mathematics education for teachers of mathematics in Namibia. This study also provided valuable insights into what such a course could look like.
Keywords: Education -- Namibia -- Case studies; Mathematics -- Study and teaching -- Namibia -- Case studies; Mathematics teachers -- Training of -- Namibia -- Case studies; Teacher educators -- Training of -- Case studies; Teachers -- Training of -- Namibia -- Case studies